Confectionery in Ukraine: adoption of european food tradition - Levitska, Nadiia; Kotsuibanska, Olga (My University, 2020)
Objective is to analyze the adaptation of European food traditions in Ukraine on the example of the historical development of the confectionery industry. Methodology of the research ‒ the principle of historicism, which allowed us to reveal the ways of transfer and transformation of food traditions. The scientific novelty is to find out the type of conversions, the quality and nature of borrowings, examples of local adaptation, and their historical background. Conclusions. 1. An industrial revolution that needed mass consumption and, accordingly, could provide cheap counterparts to traditional sweets played a significant role in adaptation. 2. The raw material basis for the development of the industry was formed only during the nineteenth century. 3. The location of Ukraine at the crossroads of geopolitical interests has shaped different spheres of influence, and, accordingly, the variety of regional sweets, which is later preserved in the factories range. Thus, the Ottoman rule in the Northern Black Sea, despite the recolonization of the region after the Russo-Turkish wars, has preserved the traditions of Eastern sweets in the culture of the Ukrainian South. 4. Based on the analysis of archival documents and periodicals, an analysis of the assortment of confectionery factories of Ukraine was made, which made it possible to compare them with the corresponding assortment of European factories and to trace the interweaving of the local food tradition and its combination with the European traditions (for example, Ukrainian adaptation of biscuits and local traditions in forming a recipe of Ukrainian gingerbread compared to Polish and English analogues of this product). 5. Spreadingof chocolate technologies was a multilayered process: those technologies were transported from Vienna to Poland and Ukraine actually at the same time. Thus,we got a blossoming industry of chocolate making in Lviv. On the other hand, the transition from the craft to the factory stage of the development of the industry was far more difficult in Western Ukraine, due to position of this region as an agrarian in the common structure of the Austro-Hungarian Empire. Мета дослідження – проаналізувати адаптацію європейських харчових традицій в Україні на прикладі історичного розвитку кондитерської галузі. Методологія дослідження – принцип історизму, який допоміг нам послідовно розкрити шляхи передачі та трансформацію харчових традицій. Наукова новизна полягає у з’ясуванні типу перетворень, якості та характеру запозичень, прикладів місцевої адаптації та їх історичного підґрунтя. Висновки. 1. Визначну роль в адаптації відіграв промисловий переворот, котрий потребував масового споживача та, зрозуміло, міг забезпечити дешевими аналогами традиційних солодощів. 2. Сировинне підґрунтя для розвитку галузі сформувалося лише у ході ХІХ ст. 3. Розташування України на перехресті геополітичних інтересів сформувало різні сфери впливу, і, відповідно, розмаїття регіональних солодощів, що пізніше збереглося і у фабричному асортименті. Так, панування Османської імперії у Північному Причорномор’ї попри реколонізацію цього регіону після російсько-турецьких війн зберегло традиції східних солодощів у культурі українського Півдня. 4. На основі аналізу архівних документів та періодичних видань охарактеризовано асортимент кондитерських фабрик України що дало підставу порівняти їх із відповідним асортиментом фабрик європейських, прослідкувати сплетіння місцевої харчової традиції та її поєднання із загальноєвропейськими традиціями, як, наприклад, українська адаптація бісквіту та традиції вживання вторинних злаків при формуванні рецептури пряника українського в порівнянні із польськими та англійськими аналогами цього виробу. 5. Проведено аналіз запровадження і розповсюдження інновацій на прикладі технології шоколаду, що одночасно набув поширення у Західній Україні та Польщі, просуваючись від Відня як тогочасного центру кондитерських інновацій. Водночас перехід від фабрично-мануфактурної, до фабричної стадії розвитку галузі проходив у Західній Україні значно важче, позаяк зумовлювався аграрно-сировинним спрямуванням цього регіону у структурі Австро-Угорської імперії.
Keywords: кафедра гуманітарних дисциплін; confectionery industry; food traditions; sweets; industrial revolution; transformation; кондитерська галузь; харчові традиції; солодощі; індустріальна революція; трансформація